Combined core promoter mutations and pre‐S deletion of HBV may not increase the risk of HCC: a geographical epidemiological study in Guangxi, China. (21st March 2013) - Li, Guo‐Jian; Harrison, Tim J.; Yang, Jin‐Ye; Chen, Qin‐Yan; Wang, Xue‐Yan; Fang, Zhong‐Liao
Abstract Background Although persistent hepatitis B virus (HBV) infection is a major cause of hepatocellular carcinoma (HCC), the mechanisms of oncogenesis remain obscure. Aims To determine whether the findings that HBV basal core promoter (BCP) A1762T, G1764A double mutations, pre‐S deletions and a combination of both are risk factors of HCC are supported by geographical epidemiology. Methods Study subjects were recruited from Long An county, where the incidence of HCC is the highest, and five other counties in Guangxi, where the HCC incidence is lower and varies among them. The Pre‐S region and BCP of HBV from all study subjects were amplified and sequenced and the data were analysed using chi‐squared tests. Results The prevalence of BCP and pre‐S mutations differs significantly (χ2 = 9.850, 5.135, respectively, all P < 0.01) between Long An and the other counties. However, the prevalence of combined BCP and pre‐S mutations does not differ significantly (χ2 = 1.510, P > 0.05). These mutations are less frequent in the young but the prevalence of pre‐S deletions does not increase with age. The prevalence of these mutations does not differ significantly between men and women but is significantly higher in Zhuang than the other ethnic populations. Among the other five counties, the prevalence of BCP mutations in counties where the HCC incidence is high is significantly higher than that of counties where the HCC incidence is low. Conclusions Combined BCP double mutations and pre‐S deletion may not increase the risk of HCC, although these mutations are a risk factor of HCC when they present alone.